Swimming in to Olympism and saving lives - Schaetz, Stacy (Πανεπιστήμιο Πελοποννήσου, 2016)
Swimming has long been deeply rooted in the history of human nature and its culture is influenced by societal norms at large as well as influencing and challenging these conceptions. The state of the world can often be mirrored in the waters we swim reflecting societal norms and conventions within any particular culture at any given time in history. Swimming can be utilized for multiple purposes like exercise, health, competition, recreation, and survival. Sadly, there is a large percentage of people who cannot actually swim, even if their life depended on it. Included in this percentage are certain ethnic and socioeconomic populations that are especially impacted by their lack of swimming skills. In many minority and special needs communities, drowning has become a growing epidemic and is claiming underserved lives across the world. Drowning currently kills more poor children than ever before, yet could be solved by cooperative initiatives for diversity and inclusion within the swimming community. This preventable public health crisis kills millions each year and is perpetuated by factors such as the high costs associated with the sport, cultural stereotypes, even the right to accessibility to clean and safe water. The power of swimming is transformational and recommended for childhood health and development, yet water safety remains elusive to so many children around the globe as evidenced by the rise and fear of the global drowning epidemic. The swimming community and all its stakeholders need to rally their pioneers and ambassadors for the sport, once again, to swim upstream, united together against the resistance of current cultural prejudices and fatal misconceptions that continue to deny the holistic benefits of swimming. This paper will examine the benefits of swimming and show that teaching young people to swim will lead to improved physical and physiological outcomes for the individual swimmers, to reduced numbers of drowning fatalities, and to improved conditions for the planet. Swimming is not just a sport, or healthful activity, it is survival skill, a tool for enhancing the quality of life. Swimming, a life skill that is for the sake of our survival, as well as, for the joy and well-being of Swimming into Olympism and Saving Lives v humanity, just as it is for conserving the environmental health of our future and planet. Water is paramount for survival yet the drowning risks are real. The disparities between race and gender statistics are known, so it is time to shed light on the murky waters that have kept swim education elusive and drowning risks on the rise in the many segments of the population one splash at a time. It is time to revisit the notion that swimming is far more than a sport, it is a life skill that is a basic human right that every man, woman and child has the right to learn as well as enjoy for a healthier life.
Keywords: Swimming - Safety measures; Swimming - Study and teaching; Swimming - Training; Swimming for children - Training; Swimming for people with disabilities; Swimming - Therapeutic use; Κολύμβηση - Μέτρα ασφαλείας; Κολύμβηση - Μελέτη και διδασκαλία; Κολύμβηση - Εκπαίδευση; Κολύμβηση για παιδιά - Εκπαίδευση; Κολύμβηση για άτομα με ειδικές ανάγκες; Κολύμβηση - Θεραπευτική χρήση; Swimming education; Equality; Diversity; Safety; Εκπαίδευση για κολύμπι; Ισότητα; Ποικιλία; Ασφάλεια